MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN METODE EKSPERIMEN PADA MATA PELAJARAN IPA KELAS V SDN 014648 PADANG MAHONDANG - Ermaliana Waruhu (JURNAL TEMATIK, 2020)
The purpose of this study was to determine the use of experimental methods to improve student learning outcomes in science learning in class V SDN 014648 Padang Mahondang. This type of research is classroom action research. This research was conducted in 2 cycles. The research subjects were students in grade V SDN 014648 Padang Mahondang, totaling 25 students. Data collection instruments used were written tests in the form of multiple choices, observation sheets, observations of teacher and student activities, and photo results. The results of the study stated that learning science through experimental methods can improve learning outcomes in science subjects. This is evident in the initial conditions before completing the action percentage of 28% completeness, the first cycle of 56% completeness percentage, completeness learning cycle I still has not been achieved. In the second cycle the percentage of completeness was 92%. In this second cycle learning completeness has been achieved. Based on the actions taken, it can be concluded that using the experimental method can improve the